Using Action Research to Improve Hand Washing among Staff and Pupils of St. Paul Primary School Nsambya, Makindye Division – Kampala District, Uganda. - Nvule, Henry Pecos; Kiconco, Arthur (Student's Journal of Health Research Africa, 2021)
Background: Many private and public schools in Kampala and Nsambya specifically do not provide soap and water at schools near toilets or pit latrines for hand washing. Even though some schools do provide these supplies, problems such as vandalism by pupils make it difficult to maintain them, thereby preventing consistent and effective hand washing by pupils. This action research carried at St. Paul primary school was done to address the most common health problem of hand hygiene, and ways of how to improve hand hygiene. Methodology: Meetings, interviews, and a focus group discussion were the methods used for data collection. Respondents were administrators, headteacher, support staff, and pupils at St. Paul primary school Nsambya, Makindye Kampala districts. Qualitative content analysis was used to explore stakeholders' experiences. Results: A total population of 670 that include the pupils, teachers, and support staff, out of the total population, 652(97.3%)are pupils (376 girls and 275 boys as displayed on the notice board), 15 (2.2%) are teachers and 3 (0.5%) are support staff. Health challenges included lack of sanitary pads for the girls which makes them uncomfortable at school, hunger at school since no meals are provided at school, over falling sick and lack of medical care at school, Pupils are sent to a nearby hospital, poor hygiene of some members of the community. Conclusion and recommendations : Stakeholders were awakened by the approach, as they were more responsive to health challenges and possible local solutions. Nonetheless, the use of participatory action was considered in full knowledge of the undesirable and complex experiences, such as uncertainty, conflict, and stress. For maintenance of handwashing supplies and providing ongoing education to promote effective hand washing among pupils was communicated to the pupils and school management.